Complex sleep‐disordered breathing after vagus nerve stimulation: broadening the spectrum of adverse events of special interest. Issue 6 (21st January 2021) - Oliveira Santos, Miguel; Bentes, Carla; Teodoro, Tiago; Moreira, Susana; Marques, Marta; Tomé, Diogo; Peralta, Ana Rita
Abstract: Two young males with refractory epilepsy of unknown aetiology were referred for vagus nerve stimulation (VNS). Sleep disturbances emerged following VNS parameter changes. In Patient 1, video‐polysomnogram (PSG) disclosed snoring and catathrenia in non‐REM sleep. Central apnoea also occurred, but more rarely. In Patient 2, video‐PSG showed mixed apnoea with desaturation and episodes of stridor followed by a catathrenia‐like sound. A drug‐induced sleep endoscopy (DISE) revealed, during VNS OFF time, glossoptosis, "trap door" of the epiglottis, and paresis of the left side of the larynx and ipsilateral vocal cords. During ON time, there were periods of pharyngeal collapse, in which video‐PSG revealed patterns suggestive of both obstructive and central sleep apnoea. All these sleep‐related phenomena were coincident with VNS ON time. In the first patient, VNS parameter adjustment was sufficient to successfully reverse all the symptoms, whereas the other patient required concomitant treatment with continuous positive airway pressure. The data broaden our knowledge about sleep disorders related to VNS, in particular stridor and catathrenia. We suggest that central sleep apnoea may be associated with laryngeal occlusion. DISE may be considered in selected cases as a valuable clinical tool to evaluate, in a single session, the effectiveness of multiple VNS parameter changes on respiration and laryngeal side effects. [ Published with video sequences ].